2010
DOI: 10.3174/ajnr.a2008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Inflow Pulsed Arterial Spin-Labeling Reveals Delays in the Arterial Arrival Time in Minor Stroke and Transient Ischemic Attack

Abstract: SUMMARY:Our purpose was to use multiple inflow pulsed ASL to investigate whether hemodynamic AAT information is sensitive to hemispheric asymmetry in acute ischemia. The cohorts included 15 patients with acute minor stroke or TIA and 15 age-matched controls. Patients were scanned by using a stroke MR imaging protocol at a median time of 74 hours. DWI lesion volumes were small and functional impairment was low; however, perfusion abnormalities were evident. Prolonged AAT values were more likely to reside in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 12 publications
5
108
0
4
Order By: Relevance
“…These results extend the work of previous clinical ASL studies 2,[5][6][7][19][20][21] by showing that CBF is reduced in the VB circulation in patients compared with controls. Significance of ASL fitting was assessed voxelwise using the 95% confidence intervals produced from the ASL model fitting.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results extend the work of previous clinical ASL studies 2,[5][6][7][19][20][21] by showing that CBF is reduced in the VB circulation in patients compared with controls. Significance of ASL fitting was assessed voxelwise using the 95% confidence intervals produced from the ASL model fitting.…”
Section: Discussionsupporting
confidence: 80%
“…This approach is justified for healthy patients but might be problematic in cerebrovascular diseases where arterial flow is atypical or delayed, as in the case of ischemic scenarios. 2,4 Recent work illustrates the value of multiple inflow ASL to extract both CBF and ATT information [5][6][7] The current study focused on symptomatic VB circulation. In contrast to carotid circulation, the impact of stenotic disease on brain perfusion in VB circulation has not been reported in the literature thus far.…”
mentioning
confidence: 99%
“…Clinically, ASL has been used to show perfusion deficits in acute (MacIntosh et al, 2010b) and chronic (Brumm et al, 2010) stroke and VASO has been successfully applied in studies of ischemic steno-occlusive disease (Donahue et al, 2009c(Donahue et al, , 2010. However, no fMRI activation studies have directly compared BOLD with these new fMRI techniques, nor evaluated their feasibility or added value in chronic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previous work by Bokkers et al, 16,29 Hendrikse et al, 30 and Macintosh et al, 17 this study demonstrates the feasibility of ASL with multiple TIs to measure perfusion and its temporal characteristics. Whereas previous studies included symptomatic patient populations, this study was the first to assess cerebral perfusion and its temporal characteristics in an asymptomatic patient population in whom increased delay time particularly is a reflection of the elongated route via collateral pathways.…”
Section: Discussionmentioning
confidence: 89%
“…14,15 Bokkers et al 16 were the first to use this technique in patients with symptomatic carotid artery occlusion and measured significant differences in CBF and timing parameters between hemispheres ipsilateral and contralateral to the occlusion side. Recently, a similar technique was used by Macintosh et al, 17 who found that prolonged arterial arrival times resided in the affected hemisphere of patients with minor stroke or transient ischemic attack, though functional impairment and lesions on diffusion-weighted imaging were limited.…”
mentioning
confidence: 99%